KETETAPAN HUKUM DAN REKONSTRUKSI PARAMETER HILAH PADA PRAKTIK PERBANKAN SYARIAH - Diky Faqih Maulana; Abdul Rozak (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2021)
Many Islamic bank products and contracts are not in accordance with sharia principles. This research will discuss in detail the related hilah in Islamic banking practices and the differences in bank interest with margins, fees, and profit sharing on Islamic bank financing. This research is a qualitative research which is literature study. The results showed that the use and parameters of hilah in syari'ah banking were different and it could be measured to what extent the practice violated the principles of syari'ah or not. Basically, the profit-sharing system, fees and margins are designed to bridge anti-usury groups, but not a few of the syari'ah banks use law to wrap a product or contract with the syari'ah label because in practice it is far from theory and principle. shari'ah. The standard of hilah, where a contract or product must meet Qasd al-shari ', Qasd al-mukallaf, Wasa'il, Maslahah, Rukhsoh and Azimah. If a contract or product meets the five parameters above then it is categorized as masyru'ah (which is permissible), but if it does not fulfill it, even the opposite, it is classified as mazmumah (which is prohibited).